Hierarchical decision-making problems: Modeling and solutions - Tadeusz Krupa; Teresa Ostrowska (Foundations of Management, 2016)
Article illustrates the state of the work conducted at the Faculty of Management Warsaw University of Technology on the issue of modeling hierarchical decision-making problems in the context of administrative and infrastructural conditions of the various forms of public safety. The aim is to develop a universal methodology of conduct for the management needs of the public administration, whose powers are focused on maintaining the continuity of the critical infrastructure of the State. The key issues covered by the article are: modeling of hierarchical issues and decision-making processes in the multi-layered organizational structures; harmonization of scales significance of decisionmaking areas with significance weights of elementary decisions in these decision areas; and a priori contradictions of elementary decisions from different decision areas and value assessments of taken problem decisions.
Keywords: 650; flat and hierarchical decision problem; standardization and harmonization of weights significance areas of decision-making; problem decisions and elementary decisions; cumulative value of problem decision; inner and inter-territorial a priori contradictory elementary decisions formalization of decision making process in hierarchical structure